Clinical Overview of Prescription of Promoting Blood Circulation and removing blood stasis in Treating Diabetic Nephropathy. Issue 3 (March 2021) - Wang, Runxi; Tian, Chunhong; Liu, Yuexuan; Lou, Qianye; Yang, Mengjie; Si, Guorui; Cai, Ruijuan; Wang, Ru; Cui, Yangqing; Fang, Yan; Wang, Jing Huan; Xing, Zhiyu; et al.
Abstract: Promoting blood circulation and removing blood stasis is an important method of clinical treatment of diabetic nephropathy (DN). Such prescriptions or compound prescriptions have a definite effect after long-term clinical practice. The Prescription of Promoting Blood Circulation and removing blood stasis (PBCRBS) reviewed in this article can improve glucose and lipid metabolism disorders, inhibit the changes in inflammation and promote blood flow of DN, reduce the burden on the kidneys, and delay the pathological changes of DN. This article summarizes the PBCRBS Clinical Overview of prescription in Treating Diabetic Nephropathy.